What drives inflation? Disentangling demand and supply factors - Sandra Eickmeier; Boris Hofmann (Deutsche Bundesbank, 2022)
We estimate indicators of aggregate demand and supply conditions based on a structural factor model using a large number of inflation and real activity measures for the United States. We identify demand and supply factors by imposing theoretically motivated sign restrictions on factor loadings. The results provide a narrative of the evolution of the stance of demand and supply over the past five decades. The most recent factor estimates indicate that the inflation surge since mid-2021 has been driven by a combination of extraordinarily expansionary demand conditions and tight supply conditions. We obtain similar results for the euro area, but with a somewhat greater role for tight supply consistent with the greater exposure of the euro area to recent adverse global energy price shocks. We further find that tighter monetary policy and financial conditions dampen both demand and supply conditions.
Keywords: E3; E5; E6; C3; 330; inflation; aggregate demand and supply; factor model; sign restrictions; monetary policy